2007
DOI: 10.1007/s11517-006-0138-x
|View full text |Cite
|
Sign up to set email alerts
|

Embryological development of pacemaker hierarchy and membrane currents related to the function of the adult sinus node: implications for autonomic modulation of biopacemakers

Abstract: The sinus node is an inhomogeneous structure. In the embryonic heart all myocytes have sinus node type pacemaker channels (I (f)) in their sarcolemma. Shortly before birth, these channels disappear from the ventricular myocytes. The response of the adult sinus node to changes in the interstitium, in particular to (neuro)transmitters, results from the interplay between the responses of all of its constituent cells. The response of the whole sinus node cannot be simply deduced from these cellular responses, beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Cholinergic receptor stimulation causes some SAN cells to become silent, which contributes to a rate decrease as proposed by Fenske et al [9]. Still other areas may be unresponsive to acetylcholine [44]. Using small tissue pieces dissected from rabbit SA node, Opthof et al [45] found that SA node pieces bordering the left atrium were quiescent when dissected, but became activated to fire APs in the presence of adrenaline or acetylcholine.…”
Section: A Broader Interpretation Of Our Results Toward Synchronization Mechanisms Of Cell Signaling In Intact San: Cell Specialization Amentioning
confidence: 97%
“…Cholinergic receptor stimulation causes some SAN cells to become silent, which contributes to a rate decrease as proposed by Fenske et al [9]. Still other areas may be unresponsive to acetylcholine [44]. Using small tissue pieces dissected from rabbit SA node, Opthof et al [45] found that SA node pieces bordering the left atrium were quiescent when dissected, but became activated to fire APs in the presence of adrenaline or acetylcholine.…”
Section: A Broader Interpretation Of Our Results Toward Synchronization Mechanisms Of Cell Signaling In Intact San: Cell Specialization Amentioning
confidence: 97%
“…It is well documented that I f and the expression of the main ventricular HCN isoforms 2 and 4 are significantly increased in ventricular moycytes of heart failure patients 5,11,28 . These changes are considered reminiscent of the immature myocytic phenotype, based on the fact that during pathological remodeling several early genes reappear in reverse order compared to embryonic development 29 . To mimic maladaptive upregulation of HCN4 in our model, the cTNI promoter was used to activate hHCN4 transcription from the intermediate-late phase of fetal development on 30 , leading to augmented levels in the myocardium throughout postnatal and adult stages, normally characterized by low HCN4 expression 6 .…”
Section: Discussionmentioning
confidence: 99%
“…The SAN is heavily innervated, with a complex network of nerve fibers and ganglia whose density is much higher than the surrounding myocardium (Roberts et al, 1989;Chow et al, 2001;Newton et al, 2014;Pauza et al, 2014;Stoyek et al, 2015;Inokaitis et al, 2016). Yet the SAN is not ubiquitously innervated and this, along with variable receptor densities throughout the node, make it functionally heterogeneous (MacKaay et al, 1980;Opthof, 2007). Sympathetic control will dominate in heavily innervated regions and areas with high receptor density, whereas these regions may be silenced by parasympathetic control, such that areas with fewer receptors or little innervation would then determine rate.…”
Section: Resultsmentioning
confidence: 99%